A whole plant analysis of the dynamics of expansion of individual leaves of two sunflower hybrids - Dosio, Guillermo (2003)
Common features in the time-course of expansion of leaves which considerably differed in final area, due to phytomer position, growing conditions and geno type, were identified. Leaf development consisted of two phases of exponential growth, followed by a third phase of continuous decrease of the relative expansion rate. The rate and the duration of the first exponential phase were common to all phytomers, growing conditions and genotypes. Leaves differed in the rate and the duration of the second exponen tial phase. The decrease of the relative expansion rate during the third phase depended on neither gen otype nor growing conditions. It was phytomer dependent and was deduced from the rate of the sec ond phase via a parameter common to all cases stud ied. Differences in ®nal leaf area among growing conditions were linked to different expansion rates during the second exponential phase. The duration of the phases at any given phytomer position was the same for the two hybrids in different growing conditions. The dates of developmental events (initi ation, end of the two exponential phases, full expan sion), and the rate of the second exponential phase, were related to phytomer position, defining a strict pattern of leaf development at the whole plant level. Using this framework simplified the analysis of the response of leaf expansion to genotype and environ ment.